Changes in Skin Surface Temperature at An Acupuncture Point with Moxibustion. Issue 2 (June 2013) - Lin, Li-Mei; Wang, Shu-Fang; Lee, Ru-Ping; Hsu, Bang-Gee; Tsai, Nu-Man; Peng, Tai-Chu
Objective: This study evaluates the thermographic changes associated with moxa burner moxibustion at the SP6 acupuncture point to establish an appropriate, safe distance of efficacy for moxibustion. Methods: Baseline temperature changes using a moxa burner were obtained for a paper substrate at various distances and times, and the tested with volunteers in a pilot study. A single-group trial was then conducted with 36 healthy women to monitor temperature changes on the body surface at the acupuncture point (SP6). Results: Based on the temperature changes seen for the paper substrate and in the pilot study, a distance of 3 cm was chosen as the intervention distance. Moxibustion significantly increased the SP6 point skin surface temperature, with a peak increase of 11°C at 4 min (p <0.001). This study also found that during moxibustion the temperature of the moxa burner's rubber layer and moxa cautery were 56.9±0.9°C and 65.8±1.2°C, as compared to baseline values of 35.1°C and 43.8°C (p<0.001). Conclusions: We determined 3 cm was a safe distance between the moxa burner and acupuncture point. Moxibustion can increase the skin surface temperature at the SP6 point. This data will aid traditional Chinese medicine (TCM) practitioners in gauging safer treatment distances when using moxibustion treatments.